2017
DOI: 10.1080/21691401.2017.1355311
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and cytotoxicity analysis of cationic lipids-mediated gene transfection into AGS gastric cancer cells

Abstract: In this effort, we provided comparative study on optimization of transfection conditions for AGS human gastric cancer cell line using two commercial non-liposomal cationic lipids. Using reporter vector pEGFP-N1, transfection efficiency of Attractene™ and X-tremeGENE HP™ transfection reagents in terms of cell densities and DNA/reagent ratios was determined in AGS cells by flow cytometry and fluorescence microscopy. In addition, influence of transfection reagents on direct cytotoxicity and cell viability was res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…These fi ndings are consistent with other studies on cytotoxicity effect of Turbofect (8). Although there are many reports about the cellular toxicity of Lipofectamine 2000 in comparison with other transection reagents such as Turbofect, there are just few published studies on toxicity of Lipofectamine 3000 (9,19,(20)(21)(22)(23). In one study, Lipofectamine CRISPRMAX was compared with Lipofectamine 3000 and Lipofectamine RNAiMAX, and signifi cant effi ciency with less toxicity of Lipofectamine CRISPRMAX was shown (12,(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 80%
“…These fi ndings are consistent with other studies on cytotoxicity effect of Turbofect (8). Although there are many reports about the cellular toxicity of Lipofectamine 2000 in comparison with other transection reagents such as Turbofect, there are just few published studies on toxicity of Lipofectamine 3000 (9,19,(20)(21)(22)(23). In one study, Lipofectamine CRISPRMAX was compared with Lipofectamine 3000 and Lipofectamine RNAiMAX, and signifi cant effi ciency with less toxicity of Lipofectamine CRISPRMAX was shown (12,(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 80%
“…It has previously revealed that the prevalence of TAFs was closely correlated with the potential of gastric cancer metastasis [35]. Moreover, TGF-b and FGF-7 produced from fibroblasts could increase gastric cancer cell proliferation and invasiveness [36,37]. Several reports have also demonstrated the TAFs express MCP-1/CCL2 when co-cultured with cancer cells and induce cell survival and immunosuppression [26,38].…”
Section: Discussionmentioning
confidence: 98%
“…An AGS (gastric adenocarcinoma) cell line and XTT method was selected for cytotoxicity studies as described before in literature [13]. Cells were cultured in a DMEM-F12 medium (supplemented with 10% foetal bovine serum, penicilliumstreptomycin) at 37 C with 5% CO 2 .…”
Section: Cytotoxicity Experimentsmentioning
confidence: 99%